Financial Performance, Capital Structure, and Company Value Comparison - Clara Neltje Meini Rotinsulu (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
The goal of this study is to compare the financial performance, capital structure, and firm values of family versus non-family firms listed on the Indonesia Stock Exchange between 2020 and 2022. In this study, purposeful sampling was used, and data was analyzed using a pairwise sample methodology, comparing family and non-family firms. There is no difference in finance performance as measured by sales growth, sales, return on assets (ROA), return on equity (ROE), gross profit margin (GPM), and net profit margin (NPM), according to the findings of this study, but there are significant differences in total asset turnover (TATO). According to the capital structure, there is no difference in firm value as proxied by earnings per EPS share between family and non-family firms.